Sage and Perfection: A Comparison Between the Human Nature & Moral Cultivation Theory of Confucian Culture and the Christian Theory of Human Nature & Salvation - TANG, Shiwen (Journal of Research for Christianity in China (JRCC), 2025)
The theory of human nature is the starting point and theoretical foundation for the moral cultivation of Confucian culture and Christian salvation. Different acknowledgement of the theory of human nature will inevitably lead to different understandings of the theory of moral cultivation and salvation. This article attempts to compare the human nature and moral cultivation theory of Confucian culture with  Christian theory of human nature and redemption and find their similarities and differences. The article will discuss the issue from three aspects: The first is to analyze the theory of human nature and moral cultivation of Confucian culture. Mencius of Confucianism believes that human nature is inherently good, if only one retrieves the goodness of human nature and cultivates it, one can become a sage. The Confucian Xunzi believes that human nature is inherently evil, through human efforts of turning evil into good, one can become a sage. The second aspect is to analyze the Christian theory of human nature and redemption. Christianity insists that at the beginning of the creation, human nature is good, but since Adam and Eve’s fall, the first ancestors of humankind who were tempted by the devil to abuse their free will, the evil thoughts have arisen in human nature. Human nature became a mixture of good and evil, causing people to be incapable of doing good. Only by relying on the salvation of Jesus Christ, one can be released from the bondage of sin; and through the indwelling and sanctification of the Holy Spirit, and the continuous efforts of humankind, one can achieve perfection. The third aspect is to compare the theory of human nature and moral cultivation in Confucian culture with the theory of human nature and redemption in Christianity. And it points out that the Christian theory of human nature and redemption can make up for the lack of the concept of sin in Confucian culture, and it can fulfill the moral ideals of Confucian culture by the redemption of Christ. Generally speaking, Confucian culture does not have the concept of original sin and redemption. Instead, it affirms the goodness in human nature and believes that people can save themselves. Christianity insists that since the fall of the ancestors of humankind, there is both good and evil in human nature. Since the evil is the sinful nature of humankind, so human beings cannot get rid of this sinful nature by themselves and be in need of Christ’s salvation. One cannot save oneself! One can only be saved by Jesus Christ. After being saved, one still needs to work hard. And with God's help, one can reach perfection finally. Confucian culture is too optimistic about human nature, emphasizing that self-salvation can be achieved through moral cultivation, it lacks the concept of sin and salvation. Christian theory of human nature and redemption can make up for the shortcomings of Confucian culture, and provide people with a belief resource and internal motivation to fulfill the moral ideals of Confucian culture, thereby contribute to the construction of Chinese ethics and morality for the nation.